Association between family functioning and depressive symptoms in medical students at a private university - Zapata-Vilcahuamán, Ever (2023)
Objective: To assess the association between global family functioning and depressive symptoms in a sample of human medicine students. Materials and methods: A cross-sectional study was carried out in 95 medical students at a private university in Lima, Peru, who participated in a virtual survey to collect clinical and sociodemographic data. Frequencies and percentages were used for the descriptive analysis, and the Mann-Whitney and Kruskal-Wallis U tests for the bivariate analysis. To assess the correlation between depression scores and family functionality, the Spearman's correlation test was used, whereas the factors associated with the score of depressive symptoms were evaluated through multiple linear regression tests. Results: Global family functionality was a negative predictor of depressive symptoms (ß = -7.91; p = 0.002), and the number of types of stressful life events (ß = 5.25; p = 0.001) constituted a positive predictor. Conclusion: Independently from other factors, medical students with higher scores of family functionality in this study, have lower scores for depressive symptoms.